Investigating the relationship between speaking fundamental frequency and acoustic vowel space size - Tseng, Felicia Hui Juan (Nanyang Technological University, 2023)
Female speakers are observed to have larger acoustic vowel space areas on average, a feature that is suggested to increase perceptual contrast as compensation for poorer resolution of the spectral envelope resulting from a higher fundamental frequency (f0). The present study investigates a potential relationship between mean speaker f0 and acoustic vowel space size as defined by the first two vowel formants. Fundamental frequencies and acoustic vowel space correlates of 16 Singapore English speakers are measured and analyzed alongside the potential impact of different speaking styles. Two parameters are used to characterize the dimensions of the vowel space: vowel space size as estimated by convex hull area calculations, and degree of vowel peripherality measured through mean Euclidean distances from the vowel space centroid. Results reveal an unexpected lack of significant difference between male and female acoustic vowel space sizes. No relationship was found between fundamental frequency and either vowel space metrics in the male group, but a correlation could be established between f0 and degree of vowel peripherality in the female group. However, issues with the sampling distribution indicate that this association may not hold up under scrutiny.